Sharing Knowledge melalui Sosialisasi Pengelolaan Sampah Plastik di Propinsi Sulawesi Tenggara - Fathun, Laode Muhamad (LPPPM STAI Darul Hikmah Bangkalan, 2021)
This paper writes about the management of plastic waste in Southeast Sulawesi Province, a case study in Muna and Buton Regencies. This activity is in the form of sharing the author's knowledge with the Indonesian City Diplomacy Community partners in 2020-2021. This activity uses observation, socialization and interview methods to build the community's mindset. The author found that plastic waste management activities in Muna and Buton have been maximized. This is done because the community upholds the value of morality as a form of social responsibility. Cultural values ​​as the foundation of society in protecting the sea. This means that the authors in sharing knowledge only confirm community activities and provide little knowledge to the community. The community is very aware of protecting the sea as part of their identity, branding, and representation of toughness. The sea is the ancestral medium of the community that must be preserved as a form of appreciation. Because the sea is the source of the local community's economy. So, if the nature is damaged, it will damage the economy of the surrounding community. Dissemination and sharing of knowledge are effective because the community does not need to be equipped with much in protecting the sea. Cultural experience and moral principles guide them to be able to make the sea an asset of the future. The sea is the way humans relate to nature, natural resources.